IMPLEMENTASI BAURAN PROMOSI SEBAGAI STRATEGI KOMUNIKASI PEMASARAN MEMOPRO WEDDING ORGANIZER DALAM MENINGKATKAN KONSUMEN MEMOPRO - Nindya Amelia, Nindya Amelia (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
In an effort to market products or services, companies need to develop products or services that are unique compared to their competitors. Therefore, the right promotion strategy is needed to increase consumers in using the services of a wedding organizer.This research was conducted to understand more about the implementation of the promotion mix as part of the marketing communication strategy carried out by Memopro Wedding Organizer to promote its services and increase consumers. This study uses Kotler's and Armstrong's promotional mix theory with a qualitative descriptive research method with data collection using interviews, observation, and documentation. The selection of informants was carried out through a purposive sampling technique.The results of this study show that Memopro's advertising promotion activities are carried out through websites, online billboards, and Instagram, and promotional activities through public relations are carried out through certification, collaboration with vendors, and holding seminars. The supporting factors for Memopro's promotional activities are the portfolio and also testimonials from previous customers and the inhibiting factor is the current lack of Memopro human resources.